PERAN LINGKUNGAN KELUARGA DALAM PENDIDIKAN ANAK USIA DINI PERSPEKTIF ISLAM: STUDI SINTESIS TEMATIK - Kadar Risman; Marwah; Henny; Adnan (Al-ATHFAL: Jurnal Pendidikan Anak, 2026)
Early childhood education (ECE) represents a crucial stage in shaping children’s character, morality, and religiosity. From an Islamic perspective, the family serves as the first and primary educational institution (madrasah al-ūlā), playing a central role in nurturing Islamic values from an early age. This study aims to thematically synthesize the role of the family environment in Islamic early childhood education through a qualitative literature review. The research employed a qualitative approach using library research, analyzing scholarly journal articles and relevant academic sources on family education, Islamic education, and ECE. Data were examined using thematic analysis, including coding, categorization, and synthesis of recurring themes. The findings reveal five principal themes: the family as madrasah al-ūlā, parental role modeling in moral and religious education, internalization of Islamic values in early childhood, Islamic parenting practices supporting child development, and the synergy between families and ECE institutions. The study highlights that the quality of parenting and consistency of values within the home environment significantly influence the success of early childhood education. Theoretically, this research contributes an integrative conceptual framework to Islamic ECE studies and emphasizes strengthening family–school partnerships in value-based education.